Implementing Transparency in Cash Receipts: A Non-Profit Organization Perspective - Natasia Alinsari; Adrian Izaak Rompis; Aprina Nugrahesthy Sulistya Hapsari (Asia Pacific Fraud Journal, 2022)
This research aims to describe the implementation of the principle of transparency in the financial income management activities of GBI Bethel Area Salatiga. This research is a type of qualitative descriptive research by measuring the principle of transparency with several indicators, specifically: availability and accessibility of documents, clarity and completeness of information, process openness, and a regulatory framework that ensures transparency. Data obtained by interview, documentation in the form of financial statements, and direct observation in the process of financial management. The results show that the principle of transparency has been implemented in the process of managing financial receipts. However, there are still some risks and weak implementation of internal control which indicate that the implementation of the principle of transparency is still not optimal.